Contamination the shells of Lebanese free range chicken eggs with potential pathogens - Nawas, Tarek (2017)
Local free-range eggs in Lebanon are favored by consumers, but are often sold without prior cleaning or processing. Eggs were proved to be a major source of many enteric pathogens that can cause varying episodes of gastroenteritis, this study was designed to investigate the surface contamination of free range egg shells. The tested eggs were purchased from 11 stores located in different regions of Lebanon. The results revealed that many members of the family Enterobacteriaceae, that are present in chicken feces, including Escherichia coli, Enterobacter cloacae and others, were isolated, however it was noted that Salmonella spp. were not among the isolates. The presence of these organisms, in the eggs obtained from different areas, confirmed that there was a trend not to clean or process these eggs in any way before sending them to the stores for sale. The mere isolation of fecal organisms, indicated that the eggs can, at any time, be contaminated with Salmonella spp. and other dangerous enteric bacteria, and thus endanger the health of the customers. It is required that public health protective measures, be enforced immediately to protect the consumers from what is currently an obvious health hazard.